Death times seven - Perry, Anne, 1943-; Zackheim, Victoria (Perry, Anne. Daniel Pitt novel., 2026)
"1913: Junior attorney Daniel Pitt must step in for his friend, fellow attorney Toby Kitteridge, whose parents have been brutally attacked. Toby's mother is dead and his father, a village vicar, is barely alive. With Toby returning to the family home in rural Ipswich, struggling with grief and disbelief, Daniel remains in London to substitute for Toby and defend Peter Ward, on trial for the sexual assault and murder of a young woman. Daniel is convinced that Ward is innocent, yet the evidence seems to prove otherwise. Eager to assist, his pathologist wife, Miriam fford Croft, offers her forensics expertise and exposes a community of fellow pathologists who may have purposefully omitted information from their autopsy reports. Despite Miriam's involvement in the case, Daniel finds himself distracted by his desire to help Toby, who is too distraught to investigate the attack on his parents. And when the evidence points to Toby's father as the killer of Toby's mother, Daniel faces two of the greatest challenges of his young career: proving the innocence of both Peter Ward and Reverend Kitteridge. One mistake in London and a blameless man will hang. One mistake in Ipswich and Toby's father will go to prison for life." --